2019
DOI: 10.3390/d11030046
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Maximum Shelf Depth versus Distance from Shore in Explaining a Diversity Gradient of Mushroom Corals (Fungiidae) off Jakarta

Abstract: Many coral reef systems are shelf-based and consist of reefs that are arranged in rows parallel to the coastline. They usually show an increase in species richness in the offshore direction, coinciding with decreasing terrigenous impact and a deeper seafloor. These two conditions usually concur, which makes it less easy to distinguish how each of them influences coral diversity separately. Since reefs off Jakarta (in the Thousand Islands archipelago) are arranged in an 80 km long string perpendicular to the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…Although it remains to be verified that the observed habitat and the morphological features of F. paraancora in this study were comparatively different from the other two species (Veron 2000), the three euphylliid corals reported in the present study were found in comparatively sheltered environments. Further examination focused on turbid, sheltered environments or on the upper mesophotic zones will help us to more thoroughly understand the diversity and distributional patterns of not only the three euphylliid corals but also other zooxanthellate corals, such as mushroom corals occurring on sandy habitats (e.g., Gittenberger et al 2015;Waheed et al 2015b;Hoeksema and Suharsono 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Although it remains to be verified that the observed habitat and the morphological features of F. paraancora in this study were comparatively different from the other two species (Veron 2000), the three euphylliid corals reported in the present study were found in comparatively sheltered environments. Further examination focused on turbid, sheltered environments or on the upper mesophotic zones will help us to more thoroughly understand the diversity and distributional patterns of not only the three euphylliid corals but also other zooxanthellate corals, such as mushroom corals occurring on sandy habitats (e.g., Gittenberger et al 2015;Waheed et al 2015b;Hoeksema and Suharsono 2019).…”
Section: Discussionmentioning
confidence: 99%
“…There are many additional factors that influence the success of a bio-invasion, and in the case of alien sessile benthic invertebrates, reproductive strategies also play a critical role [ 4 ]. Mixed species assemblages are often generated through sexual reproduction [ 5 ], while monospecific aggregations result from asexual reproduction such as budding or fragmentation [ 6 , 7 , 8 ]. Reproduction strategies are pivotal to enabling invasive species to out-compete native species through overgrowth, smothering, or competitive exclusion.…”
Section: Introductionmentioning
confidence: 99%
“…Reproductive strategies also play a critical role in the success of sessile benthic invertebrates bioinvasions (Capel et al, 2017). Mixed species assemblages are often generated through sexual reproduction (Hoeksema and Benzoni, 2013), while monospecific aggregations result from asexual reproduction such as budding or fragmentation (Hoeksema, 2004;Hoeksema et al, 2019;Hoeksema and Gittenberger, 2010). Reproduction strategies are pivotal to enabling invasive species to out-compete native species through overgrowth, smothering, or competitive exclusion.…”
Section: Introductionmentioning
confidence: 99%